Utilization of Antitumor Necrosis Factor Biologics in Very Early Onset Inflammatory Bowel Disease: A Multicenter Retrospective Cohort Study From North America. Issue 1 (27th May 2022) - Kerur, Basavaraj; Fiedler, Karoline; Stahl, Marisa; Hyams, Jeffrey; Stephens, Michael; Lu, Ying; Pfefferkorn, Marian; Alkhouri, Raza; Strople, Jennifer; Kelsen, Judith; Siebold, Leah; Goyal, Alka; et al.
Abstract : Background: Research on the utilization and effectiveness of antitumor necrosis factor (TNF) biologics in children with very early onset inflammatory bowel disease (VEOIBD) is urgently needed. Here we describe anti-TNF use and durability in a multicenter cohort. Methods: We performed a retrospective cohort study of patients diagnosed with VEOIBD (<6 years) between 2008 and 2013 at 25 North American centers. We performed chart abstraction at diagnosis and 1, 3, and 5 years after diagnosis. We examined the rate of initiation and durability of infliximab and adalimumab and evaluated associations between treatment durability and the following covariates with multivariate Cox proportional hazard regression: age at diagnosis, sex, disease duration, disease classification, and presence of combined immunomodulatory treatment versus monotherapy. Results: Of 294 children with VEOIBD, 120 initiated treatment with anti-TNF therapy and 101 had follow-up data recorded [50% Crohn disease (CD), 31% ulcerative colitis (UC), and 19% IBD unclassified (IBD-U)]. The cumulative probability of anti-TNF treatment was 15% at 1 year, 30% at 3 years, and 45% at 5 years from diagnosis; 56 (55%) were treated between 0 and 6 years old. Anti-TNF durability was 90% at 1 year, 75% at 3 years, and 55% at 5 years. The most common reason for discontinuation of anti-TNF were loss of response in 24 (57%) children. Children with UC/IBD-U had lower durability than those with CD (hazard ratio [HR] 0.17; 95% confidence interval [CI], 0.06–0.51; P = 0.001). Conclusions: Utilization and durability of anti-TNF in VEOIBD is relatively high and comparable with older children. Having Crohn disease (compared with UC/IBD-U) is associated with greater durability.